Meaningful use of ursodeoxycholic acid in a young polymorbid patient with arterial hypertension, obesity, and nonalcoholic fatty liver disease: a clinical case - Olga A. Polyakova; Mariya V. Klepikova; Sergey V. Cheremushkin; Olga D. Ostroumova (LLC "MEDIAFORMAT", 2023)
Currently, polymorbidity is characteristic not only for gerontological patients, but also for persons of young and middle age, which is due to the peculiarities of modern lifestyle. In this context, diseases connected pathophysiology are of particular interest, since in this case the therapeutic treatment strategies based on the existing nosological approach may not give a proper positive result. At the same time, prescribing drugs with positive pleiotropic properties plays a very important role, as it allows to influence several pathophysiological mechanisms at once and avoid polypragmasy. In this article we consider a clinical case demonstrating the features of management tactics of a young polymorbid patient with arterial hypertension, obesity and nonalcoholic fatty liver disease, in whom the addition of ursodeoxycholic acid to the complex of therapeutic interventions gave positive effects not only in reducing the severity of liver steatosis, but also in terms of cardiovascular and metabolic disorders.